Intonation words in initial intentional communication of Mandarin-speaking children - Zhang, Yunqiu; Li, Jiantao; Zhang, Yang (Frontiers in Psychology, 2024)
Intonation words play a very important role in early childhood language development and serve as a crucial entry point for studying children’s language acquisition. Utilizing a natural conversation corpus, this paper thoroughly examines the intentional communication scenes of five Mandarin-speaking children before the age of 1;05 (17 months). We found that children produced a limited yet high-frequency set of intonation words such as “啊 [a], 哎 [æ], 欸 [ε], 嗯 [ən], 呃 [ə], eng [əŋ], 哦 [o], and 咦 [i].” These intonation words do not express the children’s emotional attitudes toward propositions or events; rather, they are utilized within the frameworks of imperative, declarative, and interrogative intents. The children employ non-verbal, multimodal means such as pointing, gesturing, and facial expressions to actively convey or receive commands, provide or receive information, and inquire or respond. The data suggests that the function of intonation words is essentially equivalent to holophrases, indicating the initial stage of syntactic acquisition, which is a milestone in early syntactic development. Based on the cross-linguistic universality of intonation word acquisition and its inherited relationship with pre-linguistic intentional vocalizations, this paper proposes that children’s syntax is initiated by the prosodic features of intonation. The paper also contends that intonation words, as the initial form of human vocal language in individual development, naturally extend from early babbling, emotional vocalizations, or sound expressions for changing intentions. They do not originate from spontaneous gesturing, which seems to have no necessary evolutionary relationship with the body postures that chimpanzees use to change intentions, as suggested by existing research. Human vocal language and non-verbal multimodal means are two parallel and non-contradictory forms of communication, with no apparent evidence of the former inheriting from the latter.